The Uses of 2-Ethoxy-(4H)-3,1-benzoxazin-4-one in the Synthesis of Some Quinazolinone Derivatives of Antimicrobial Activity - Fakhry A. El-Bassiouny; Sameh A. Rizk; Khalid M. Darwish; Maher A. El-Hashash (MDPI AG, 2011)
The behavior of 2-ethoxy-(4H)-3,1-benzoxazin-4-one (1) towards nitrogen nucleo-philes, e.g. ethanolamine, aromatic amines (namely: p-toluidine, p-anisidine, p-hydroxyaniline, o-hydroxyaniline, o-bromoaniline, o-phenylenediamine, p-phenylene- diamine, o-tolidinediamine) p-aminobenzoic acid, glucosamine hydrochloride,  2-amino- nicotinic acid, 1-naphthalenesulfonic acid hydrazide, n-decanoic acid hydrazide, benzoic acid hydrazide, semicarbazide, aminoacids (e.g. D,L-alanine, L-asparagine, L-arginine) and derivatives of 2-aminothiodiazole has been investigated. The behavior of the benzoxazinone towards a selected sulfur nucleophile, L-cysteine, has also been discussed. Formation of an amidine salt as a reaction intermediate has been assumed. The effect of solvent in some reactions has been elucidated. The structures of all the novel quinazoline and quinazolinone derivatives, obtained by heterocyclic ring opening and ring closure were inferred by the IR, MS as well as 1H-NMR spectral analysis. Moreover, the antimicrobial potential of some of the new synthesized derivatives has been evaluated.